Temporal trends in neonatal mortality in Pernambuco - Nayara Francisca Cabral de Sousa; Ana Paula Esmeraldo Lima; Vânia Pinheiro Ramos; Mônica de Avelar Figueiredo Mafra Magalhães; André Luiz Sá de Oliveira; Eliane Rolim de Holanda; Luciana Pedrosa Leal (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: To verify the temporal trend of neonatal mortality in the health regions of Pernambuco between 2000 and 2020. Method: A time-series ecological study was conducted, analyzing the total neonatal mortality rate and its early and late components. For regression analysis, Joinpoint Regression was applied, trends were classified, and annual and average percentage changes were calculated for the period, with a significance level of 95%. Results: The average neonatal mortality rate in Pernambuco was 11.5 during the studied period. A decreasing trend in neonatal mortality rate was observed, especially in the early component. The region where the state capital is located showed the fastest decrease across all components. Conclusion: The temporal trend of neonatal mortality was decreasing; however, the rate of reduction was not uniform across the health regions of the state, and the implementation of the Mãe Coruja Pernambucana Program did not impact the trend in neonatal mortality.